Documenting InStory – Mobile Storytelling in a Cultural Heritage Environment - Barbas, Helena (2014)
This paper describes the process and problems that had to be faced during the elaboration of a digital interactive narrative for the Instory project (http://img.di.fct.unl.pt/InStory/) implanted in «Quinta da Regaleira», Sintra, Portugal, and classified as World Heritage by Unesco. It also explores some of the practical and theoretical issues in what regards the literary terminology and strategies involved.